(untitled) - FOS (Illinois, 1992)
This book shows to inspect tires and tracks and diagnose problems. It gives step-by-step repair procedures; and explaining in detail how to maintain them to avoid future problems. This book is filled illustrations to clearly demonstrate what must be done... photographs, drawings, pictorial diagrams, troubleshooting charts, and diagnostic charts
Keywords: agricutural mechanics